Effects of a 6-month exercise programme on disease activity, physical and functional parameters in patients with ankylosing spondylitis: Randomised controlled trial - Kim Nolte; Dina C. Janse van Rensburg; Lizelle Fletcher (AOSIS, 2021)
Background: Exercise forms an important component in the management of ankylosing spondylitis (AS). The objective of our study was to determine the effects of a 6-month swimming, land-based stretching, strengthening and breathing exercise intervention in AS patients. Methods/design: A total of 29 (14 females, 15 males) patients diagnosed with AS according to the Modified New York Criteria participated in our study. Participants were randomly assigned to an exercise group (ASE) (16 participants) and a control group (ASC) (13 participants). Erythrocyte sedimentation rate and C-reactive protein (CRP); anthropometric measurements; pulmonary function; aerobic capacity; balance; Bath AS Metrology Index; Bath AS Disease Activity Index and the Bath AS Functional Index were assessed. Discussion: Erythrocyte sedimentation rate and CRP did not change notably within or between the groups from pre- to post-intervention. The between group analyses of the physical assessments favoured the ASE with observable improvements in chest expansion (p = 0.002), forced expiration volume (p = 0.012), absolute (p = 0.017) and relative (p = 0.003) maximal oxygen consumption, absolute (p = 0.028) and relative (p = 0.001) physical work capacity. Within the ASE, there is statistical evidence of improvements in 11 of the 19 physical variables. Within the ASC, five of the physical variables deteriorated substantially (p between 0.004 and 0.037) and only balance overall stability on the right improved (p = 0.016). The three functional assessments in the ASE improved (p 0.007) compared with the ASC post-intervention. A 6-month combined exercise programme may improve physical and functional capacity of AS patients. Conclusion: A multimodal exercise intervention may be useful in the management of ankylosing spondylitis. Clinical implications: An unsupervised well -explained exercise programme combining swimming, land-based strengthening and stretching exercises and breathing exercises may be an option for patients with ankylosing spondylitis. Trial registration: Registration not undertaken at the time of writing.